2015
DOI: 10.1186/s13024-015-0012-0
|View full text |Cite
|
Sign up to set email alerts
|

Promising cannabinoid-based therapies for Parkinson’s disease: motor symptoms to neuroprotection

Abstract: Parkinson’s disease (PD) is a slow insidious neurological disorder characterized by a loss of dopaminergic neurons in the midbrain. Although several recent preclinical advances have proposed to treat PD, there is hardly any clinically proved new therapeutic for its cure. Increasing evidence suggests a prominent modulatory function of the cannabinoid signaling system in the basal ganglia. Hence, use of cannabinoids as a new therapeutic target has been recommended as a promising therapy for PD. The elements of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(64 citation statements)
references
References 351 publications
(473 reference statements)
1
60
0
3
Order By: Relevance
“…Interestingly, cannabinoid receptor agonist WIN-55,212-2 is shown to have neuroprotective effects for Parkinson's disease, suppressing excitotoxicity, glial activation and oxidative injury of dopaminergic neurons 60 . It is possible that GPR55 may exert its effects in dopaminergic neurons to regulate physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, cannabinoid receptor agonist WIN-55,212-2 is shown to have neuroprotective effects for Parkinson's disease, suppressing excitotoxicity, glial activation and oxidative injury of dopaminergic neurons 60 . It is possible that GPR55 may exert its effects in dopaminergic neurons to regulate physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…7 | P a g e 11-hydroxytetrahydrocannabinol) have been found to be neuroprotective in preclinical models of Parkinson's disease (reviewed by More and Choi, 2015) and may also be useful in Alzheimer's disease (Ramirez et al, 2005) but this is not always the case (Chen et al, 2010). Also in the current issue, (Wilkes, 2008) and diethylpropion, used for weight loss (Cercato et al, 2009).…”
Section: Accepted Manuscriptmentioning
confidence: 90%
“…In the current issue, Mursaleen and Stamford (2015) review the utility of cannabinoids in Parkinson's disease. The evidence that they present clearly suggests that cannabinoids may be of some use, not only in treating the symptoms of Parkinson's disease, but also in reducing L-3,4-dihydroxyphenylalanine (L-DOPA)-induced dyskinesias (More and Choi, 2015). Sierradzan et al, (2001) examined the synthetic cannabinoid nabilone in Parkinson's disease and found reduced L-DOPA induced dyskinesias.…”
Section: Categories Of Nps and Their Similarity To Clinically Used Drmentioning
confidence: 97%
“…Thus development of safe, effective cannabis-based medicines targeting different mechanisms may have a significant impact in PD therapy [56].…”
Section: Cannabinoids In Parkinson's Diseasementioning
confidence: 99%